Rational construction of metal nanoparticles fixed in zeolite crystals as highly efficient heterogeneous catalysts. (June 2018) - Wang, Liang; Xu, Shaodan; He, Shenxian; Xiao, Feng-Shou
Graphical abstract: Highlights: Developments on metal catalysts fixed in zeolite crystals are summarized. The synergism of zeolite crystals and metal sites are emphasized. Challenges and perspectives for developing more effective catalysts are discussed. Abstract: The zeolites, a class of materials with uniform porosity, high crystallinity, structural diversity, and large surface area, have been extensively studied in both synthesis and applications in catalysis, separation, and adsorption. In the zeolite crystals, the uniform nanopores benefit molecular diffusion, but the absence of catalytically active metal species ( e.g. isolated metal site, nanocluster, and nanoparticle) strongly limits their wide applications. Solution to this problem is to fix the active sites inside of the nanoporous crystals. In this review, it is briefly summarized recent developments on metal-based active species fixed in zeolite crystals, including the synthesis strategies, catalytic performances, and mechanism investigations. It is emphasized that the nanoparticles of metals and metal oxides fixed inside of zeolite crystals effectively combine the advantages of high activity of the nanoparticles and the selectivity/stability of the zeolite, resulting in enhanced catalytic performances in a series of reactions. Particularly, the metal nanoparticles are effectively stabilized by the zeolite sheath, giving superior sinter resistance at harsh reaction conditions.